IoT devices deployment challenges and studies in building management system - Chan, Raymond; Yan, Wye Kaye; Ma, Jung Man; Loh, Kai Mun; Yu, Tan; Low, Malcolm Yoke Hean; Yar, Kar Peo; Rehman, Habib; Phua, Thong Chee (Frontiers in the Internet of Things, 2023)
Deployment of IoT devices into an existing control system has increasingly become a new norm in recent years. Traditional approach of installing a new device into the system involves creating a separate network or infrastructure to ensure that the newly added devices do not affect the current system. However, this may not be the optimal solution for IoT devices, as they are designed to integrate and communicate with the existing systems. Therefore, it is important to understand how to properly deploy IoT devices and address the concerns of engineers. This research shares valuable experiences in deploying and integrating IoT devices into a campus Building Management System (BMS). It covers considerations and requirements for the devices, as well as the deployment and integration challenges encountered during the process.These valuable experiences can serve as a useful reference for the industry when they need to install IoT devices in their infrastructure.